BRIEF READING, SIGNIFICANT IMPACT: THE IMPLEMENTATION OF A 15 MINUTE READING HABITUATION PROGRAM USING PICTURE STORYBOOKS TO STRENGTHEN ELEMENTARY SCHOOL STUDENTS’ CHARACTER - Yeni Yuniarti; Ai Sutini; rohaetul (SOSIOEDUKASI, 2026)
Strengthening character education at the elementary school level is increasingly important in addressing contemporary educational challenges. One practical strategy widely implemented in schools is a 15-minute reading habituation program utilizing picture storybooks. This study aims to systematically examine the contribution of short reading habituation using picture storybooks to the development of elementary school students’ character. This research employed a Systematic Literature Review (SLR) approach by analyzing relevant national and international journal articles published between 2022 and 2025. Data were collected from reputable academic databases and analyzed descriptively to identify key patterns related to literacy practices, character formation, and the pedagogical role of picture storybooks. The findings indicate that consistent short-duration reading activities effectively support the internalization of character values such as honesty, responsibility, discipline, empathy, and cooperation. Picture storybooks facilitate value transmission through narrative and visual elements that align with children’s cognitive and emotional development, enabling moral learning to occur naturally and enjoyably. In conclusion, the 15-minute reading habituation program using picture storybooks represents a simple yet sustainable literacy-based strategy for strengthening character education in elementary schools when